Exploring the Impact of Strategic Intelligence on Strategic Orientation: A Field Study on Jordanian Commercial Banks - Shukri Zarafili, Sami; Shukri Zarafili, Lina (Jordan Journal of Business Administration, 2023)
This study aimed at identifying the impact of strategic intelligence on strategic orientation in Jordanian commercial banks. The population of the study consisted of all thirteen Jordanian commercial banks. The study sample included all of the study population (a comprehensive survey). The unit of sampling and analysis totaled (870) respondents and was comprised of the following job titles: general manager, deputy general manager, department manager and branch manager in the targeted banks. In order to achieve the objectives of this study, quantitative methods (descriptive and analytical methods) were used and a questionnaire was designed to collect the required data from the respondents to test the study hypotheses using Partial Least Squares-Structural Equation Modeling (PLS-SEM). The findings of the analysis indicated that strategic intelligence has a statistically significant impact on strategic orientation in Jordanian commercial banks. Also, the findings revealed that the levels of strategic intelligence and strategic orientation in Jordanian commercial banks were high. Based on the findings, the study concluded the necessity of promoting the adoption of a high level of strategic intelligence in the targeted banks because of its significant influence on the strategic orientation of these banks